Hyperactivation of the hypothalamo‐pituitary‐adrenocortical axis in streptozotocin‐diabetic gerbils (Gerbillus gerbillus). Issue 4 (26th September 2018) - Hammadi, Soumia; Chan, Owen; Abdellali, Mohamed; Medjerab, Maha; Agoun, Hadjer; Bellahreche, Zineb; Khalkhal, Ali; Dahmani, Yasmina
Summary: This study was designed to investigate the HPA‐axis impairment in the streptozotocin (STZ)‐diabetic gerbils ( Gerbillus gerbillus ). Twenty‐six male gerbils (body weight ~27 g) were divided into 3 groups: vehicle control (n = 10), 2 days of diabetes (n = 09) and 30 days of diabetes (n = 07). The latter 2 groups received an intraperitoneal injection of STZ (150 mg/kg of body weight). At 2 and 30 days of diabetes, streptozotocin‐diabetic gerbils underwent a retro‐orbital puncture for assessment of biochemical and hormonal parameters. Subsequently the animals were decapitated and the adrenal glands were removed, weighed and processed for light microscopy and stereology. Nondiabetic control gerbils that had been injected with citrate buffer were examined as a comparison. At 2 days of diabetes, STZ gerbils exhibited symptoms that are characteristic of human diabetes type 1. The adrenal gland showed significant increase in weight, associated with a larger cortex layer, hypertrophy of the fasciculate cells and a significant decrease in the nucleocytoplasmic index. These changes were associated with higher plasma ACTH and cortisol concentrations compared to nondiabetic controls. At 30 days postdiabetes, ACTH levels remained elevated, whereas cortisol levels decreased compared to the early stage of diabetes. Histological analysis revealed the existence of a band of connective tissue (collagen) that separates the cortical and medullary zones and is not present in humans or laboratory rodents, which represents a striking change seen throughout the disease. STZ‐induced diabetes mellitus in Gerbillus gerbillus resulted in hyperactivation of the HPA axis in the early stages of diabetes mellitus which did not persist into the final stages of the disease, suggesting a possible reduction in adrenocortical sensitivity over time.